Performance and Welfare of Laying Hens Raised on Floor in Relation to Different Housing Densities - Alexander Alexandre de Almeida; Heder José D’Avila Lima; Fernanda Nunes Albernaz Silva; Marcos Vinícius Martins Morais; Debora Duarte Moraleco; Jean Kaique Valentim; Tatiana Marques Bittencourt (Acta Scientiarum. Animal Sciences, 2025)
This study analyzed the productive performance, egg quality and physiological and behavioral parameters of laying hens at different housing densities in a cage-free system, following animal welfare guidelines and improvements in animal housing in intensive systems. 252 Novogen Brown laying hens, 52 weeks old and with an average weight of 1,740 ± 0.11 kg, were used over 63 days, divided into three periods of 21 days. The study adopted a completely randomized experimental design, with four treatments and seven replications. The housing densities tested were: 6 birds box-1 (0.406 m2 bird-1), 8 birds box-1 (0.305 m2 bird-1), 10 birds box-1 (0.244 m2 bird-1) and 12 birds box-1 (0.203 m2 bird-1 bird). The data were analyzed for normality of residuals, homogeneity of variance and independence of errors, using linear and quadratic regression models for each variable. In cage-free poultry production systems, housing densities of 6 to 8 birds per box can be used without affecting performance, egg quality, physiological or behavioral parameters of the hens.